The Water Act 2003 and sustainable abstraction - Sowter, Peter; Howsam, Penny (Lawtext Publishing, 2008)
This paper traces the development of the abstraction licensing system in England and Wales from the perspective of changes to water rights. It assesses the relative effectiveness of recent changes to supporting legislation in achieving a sustainable water resource balance. Particular emphasis is placed on actions to address problems caused where licensed abstraction results in environmental damage to designated sites. Water law in England and Wales, as elsewhere, is changing, in response to increasing societal, economic and environmental pressures on the finite water resource, including those recently identified relating to climate change. The Water Act 2003 is the most recent legislation aimed at ensuring sustainable use of water resources. The 1963 Water Act was the first to require that the right to abstraction of surface or groundwater (with some exemptions) was subject to a licence. ‘Permanent’ licences conferring legal rights to take water were issued to riparian occupiers (whose right to water had hitherto been considered part of their right to land), on a ‘first come, first served’ basis, without formal guidelines for justification of required quantities. This reflected the perception of water as a free and plentiful resource, and followed the long established ‘riparian rights’ principle.[1] These riparian rights, and corresponding obligations, which had been shaped by case law, are described by Hodgson [2] as “an integral part of the right of ownership of the land in question”, and as such, the loss of that right would justify some form of compensation. Successive rounds of legislation since 1963, notably the Water Resources Acts (1989, 1991), Environment Act 1995 and most recently the 2003 Act, have increased regulatory control over abstraction (and discharges) to protect the environment as well as the rights of existing abstractors. This has been broadly in response to greater awareness of environmental impacts, the obligation to comply with European Directives, and increasing demands on water resources from a greater and more affluent population. However, none of these laws has challenged the ‘licence of right’ concept, despite the considerable (and partly unused) quantities of water ‘tied up’ in them which could arguably in some cases be more appropriately assigned for other purposes. Caponera [3] suggests that modern water legislation needs to: “replace existing….common law principles with written rules which will facilitate the most rational use of available water through appropriate administrative action”. Hodgson [4] uses the term ‘modern water rights’ for this introduction of formal and explicit water rights, and states that this approach is of benefit to all: (a) society by permitting “the orderly allocation and sustainable use of valuable water resources”; (b) the user, by providing ”the necessary security to invest in activities entailing the use of water” and (c) the regulator because the system is “legally backed”. [1] Evans, B. and Howsam, P., (2005). A critical analysis of the riparian rights of water abstractors within England and Wales. Water Law, (16), p. 90-94. [2] Hodgson, S., (2006). Modern Water Rights, theory and practice. Food and Agriculture Organisation, Rome. p.11. [3] Caponera, D., (1992). Principles of water law and administration National and Internati